A study of English literacy implementation challenges among primary school teachers in Kelantan, Malaysia - Omar, M.C; Ghazali, N.B; Saputra, J. (2021)
The implementation of LINUS program has been creating the challenges among schoolteachers, especially primary school. The challenges faced by these English Literacy teachers receive less attention from the Ministry of Education Malaysia. In achieving the Key Performance Indicators, the Ministry's program has created its challenges for these teachers. They must pay attention to the programs carried out and achieve the KPIs that have assigned. The Literacy and Numeracy Program (LINUS) in primary schools require students to master 12 constructs during screening. For English subjects, particularly the teachers who conduct this screening are optional teachers and non-optional teachers. It causes problems for these teachers to face students who have multiple abilities in the same classroom. The present study seeks to identify teachers' challenges in implementing English Literacy in primary schools. For achieving the objectives of the study, literature analysis has been selected and applied. This study found that two main factors challenge teachers in implementing English Literacy based on the analysis results. The first factor is teachers' challenge in the best management and planning to improve LINUS programs' achievement. The second factor is teacher effectiveness. It is because the effectiveness of teachers will improve the teaching performance and academic achievement of students. The MOE should give both factors attention to enhance the achievement of English Literacy in the future.